2020
DOI: 10.3171/2019.2.jns182450
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of neuromodulation devices and therapies: a patient-centered survival analysis

Abstract: OBJECTIVEDespite rapid development and expansion of neuromodulation technologies, knowledge about device and/or therapy durability remains limited. The aim of this study was to evaluate the long-term rate of hardware and therapeutic failure of implanted devices for several neuromodulation therapies.METHODSThe authors performed a retrospective analysis of patients’ device and therapy survival data (Kaplan-Meier survival analysis) for deep brain stimulation (DBS), vagus nerve stimulation (VNS), and spinal cord s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The rate of explants is one of the most important concerns, in the analysis of suitability of implanted candidates. In a study by Patel et al ,5 the main reason for the removal of the hardware was the lack of effectiveness of the stimulation (81%), and in the study from Teton et al ,6 the percentage of patients still using SCS therapy decreases by almost 15% every 5 years. In this sense, Goudman et al 2 suggested that the individual goals of patients and their level of satisfaction regarding compliance might significantly affect the SCS therapy and its outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of explants is one of the most important concerns, in the analysis of suitability of implanted candidates. In a study by Patel et al ,5 the main reason for the removal of the hardware was the lack of effectiveness of the stimulation (81%), and in the study from Teton et al ,6 the percentage of patients still using SCS therapy decreases by almost 15% every 5 years. In this sense, Goudman et al 2 suggested that the individual goals of patients and their level of satisfaction regarding compliance might significantly affect the SCS therapy and its outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of the spinal cord has long been used to effectively treat lower back pain (1) and complex regional pain syndrome (CRPS) (2). One of the challenges faced during spinal cord stimulation (SCS) therapy is loss of chronic efficacy of the treatment (3). Underlying reasons for this change of therapy may include device failure, lead migration, habituation of SCS treatment, etc (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges faced during spinal cord stimulation (SCS) therapy is loss of chronic efficacy of the treatment (3). Underlying reasons for this change of therapy may include device failure, lead migration, habituation of SCS treatment, etc (3)(4)(5). Finding a control signal that can provide necessary notification or even adjustment to treatment is necessary for long-term SCS therapy and user experience improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, private insurance companies have also tightened up their local coverage determination policies and preauthorization processes and in some cases have continued to label some devices as investigational to deny coverage. In addition, recent studies comparing the long-term outcomes and durability of treatment effect between SCS and other neuromodulation techniques to treat Parkinson’s disease or provide vagal stimulation have brought the value of SCS into question for other reasons 5. As SCS treatment continues to grow for chronic pain conditions, it is important to evaluate its use, identify trends and examine the implications of growth in cost and utilization and potential changes in access as a result.…”
Section: Introductionmentioning
confidence: 99%